Hubungan Antara Pengetahuan Pasien dan Persepsi Terhadap Kinerja Pelayanan Puskesmas di Kota Semarang - Nugroho, Septiawan Catur Adi; Erawati, Ambar Dwi; Sugiarto, Sigit; Hapsari, Wiwid putri Aprilia (LPPM Institut Pendidikan Nusantara Global, 2025)
Community Health Centers (Puskesmas) as primary healthcare facilities play a crucial role in providing basic health services to the community. As the first-level healthcare providers, Puskesmas are expected to deliver services that are high-quality, equitable, and patient-oriented. This study aims to analyze the relationship between patients’ knowledge and perceptions with the performance of Puskesmas services in Semarang City. This research employed a quantitative approach with a correlational design, involving patients as respondents. Data were collected through questionnaires and analyzed using the Pearson correlation test to determine the direction and strength of the relationships between variables. The results showed a positive relationship between patients’ knowledge and service performance, although the relationship was weak (r = 0.313; p < 0.05). In contrast, patients’ perception demonstrated a very strong and significant relationship with service performance (r = 0.944; p < 0.001). The simultaneous relationship between knowledge and perception with service performance was also positive but weak (r = 0.257; p < 0.05). These findings indicate that patients’ perception is the most dominant factor influencing service performance. Empirically, an increase in perception scores is strongly associated with improved performance scores. Therefore, efforts to enhance service quality should focus on building positive patient perceptions through fast, friendly, responsive, and informative services, along with improving health literacy to strengthen patient trust and satisfaction toward Puskesmas services.